The effect of using BCPAP in the management of Respiratory Distress - Ali Jalil Malallah Al Rubaye; Nabeel Amer Mohammed Ali Al Quraishi; Asaad Hasan Noaman (Zien Journals, 2023)
In the developing world, one of the biggest cause why infant die is respiratory distress. A noninvasive respiratory support technique called bubble continuous positive airway pressure (BCPAP) is used to treat neonates who are experiencing respiratory distress. It was originally mentioned in 1971 as a way to help premature newborns' respiration. BCPAP is a less invasive method of providing respiratory assistance to newborns than mechanical ventilation. Method: 63 babies with respiratory distress were put on BCPAP as part of a clinical trial study that was undertaken at Al-Forat Al-Awsat Teaching Hospital in An'najaf city from February 1 to June 30, 2018. Results: It was shown that although 38 patients (60.31%) with respiratory distress were helped and effectively weaned off of BCPAP, CPAP failed to help 25 patients (39.68%) with respiratory distress, and they died as a result. Conclusion: BCPAP was beneficial in treating respiratory distress.
Keywords: Continuous Positive Airway Pressure; Bubble Nasal Continuous Positive Airway Pressure